Coinfections increase the risk of HIV acquisition, AIDS progression, and therapy and prophylaxis failure: a review - Robert Root-Bernstein (Academia Medicine)
Few people exposed to human immunodeficiency virus (HIV) become infected. Among those infected, the rate of progression to full-blown acquired immunodeficiency syndrome (AIDS) and susceptibility to various opportunistic infections varies widely as does their response to antiretroviral therapies (ARTs). This review addresses these conundrums in light of Pasteur’s principle that “the terrain is as important as the germ”. Recent studies have demonstrated that the risk of acquiring an HIV infection, the rate at which AIDS progresses, and the degree to which individual patients respond to retroviral therapies are largely determined by the degrees of immunosuppression and inflammation preexisting at the time of HIV exposure. The primary drivers of preexisting immunosuppression and inflammation are non-HIV infections and possibly alloantigen and drug exposures. The immunologic insults stimulate increased C–C chemokine receptor type 5 co-expression with a cluster of differentiation 4 on monocytes and T cells, which is required for HIV infection and replication. Repeated predispository infections also degrade immune competence independent of HIV and undermine ART and pre-exposure prophylaxis effectiveness. Thus, non-HIV infections are as important to understanding susceptibility to HIV infection, its progression, and the effectiveness of treatments and prevention. Addressing these non-HIV predispository infections may provide novel preventative, diagnostic, and therapeutic opportunities.